Adequacy of Monitoring and Supervision of Public Primary Education in Ogun State, Nigeria: An Evaluation - Jayesimi, Goke (NIU Journal of Social Sciences, 2019)
The study appraised the state of monitoring and supervision of public primary schools in Ogun State, Nigeria. It adopted the descriptive survey design. The Supervision and Control of Primary Education Questionnaire (SCPEQ) was used to gather data. Data obtained were analysed using frequency count, percent, mean and standard deviation. The results show that public primary school supervision was not regular, continuous and thorough. They also reveal that there were not enough professionally trained school supervisors, and that the volume of work was so enormous that supervisors on ground were often overwhelmed. They indicate further that inspectors did not employ cooperative strategies with teachers to ensure efficient functioning of the school system and that they maintained a superior-subordinate relationship with teachers.  The study recommends the employment of professionally trained personnel in adequate number. It also suggests the provision of efficient transportation arrangement for school inspectors, especially in the rural areas, and prompt payment of travelling allowances to encourage and motive them to greater productivity. Keywords: Monitoring; Supervision; Appraisal.